2012
DOI: 10.5130/ajceb.v9i2.3017
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Governance of Australian Listed Construction Companies

Abstract: This paper compares the compliance level of Australian Stock Exchange (ASX) listed construction and non-construction companies with the ASX Corporate Governance Council (CGC) recommendations on sound corporate governance. It also examines the difference in board characteristics between the two groups, paying particular attention to differences in board independence. It concludes that compared with the top 20 ASX listed non-construction companies, listed construction companies are less compliant overall particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Which explains that corporate governance always remains a device aimed at securing and stabilizing the business situation in the face of crises and unforeseen threats. Also, this result joins that of several researchers who have shown that good corporate governance promotes effective risk management, providing the flexibility needed to respond to unforeseen threats and take advantage of opportunities (Loosemore& Tait, 2009;Liang, 2016;Armeanu, 2017).…”
Section: Discussion Of Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Which explains that corporate governance always remains a device aimed at securing and stabilizing the business situation in the face of crises and unforeseen threats. Also, this result joins that of several researchers who have shown that good corporate governance promotes effective risk management, providing the flexibility needed to respond to unforeseen threats and take advantage of opportunities (Loosemore& Tait, 2009;Liang, 2016;Armeanu, 2017).…”
Section: Discussion Of Resultssupporting
confidence: 68%
“…Indeed, a good corporate governance helps support effective risk management, which in turn provides the flexibility to respond to unforeseen threats and take advantage of opportunities (Armeanu, 2017). Research by Tait & Loosemore (2009) shows that good corporate governance is linked to higher levels of organizational resilience resulting from the benefits financial instruments for investors (Armeanu, 2017). Also, Liang.…”
Section: Governance Factorsmentioning
confidence: 99%
“…Further, the research of Tait and Loosemore [10] underlined that sound corporate governance is related to higher levels of organizational resilience ensuing from the reputational and financial benefits of better transparency, market value, investor attractiveness, and organizational performance. Liang et al [11] noticed that the fundamental corporate governance indicators towards business failure examination were board composition and ownership structure.…”
Section: Introductionmentioning
confidence: 99%
“…Corporate governance is defined as a system where business company is directed and controlled (Kajola, 2008). The structure of optimum modal including some debt which is not 100% debt is the best ratio debt/equity for company minimalizing payment and reduce the probability of bankruptcy (Obradovich & Gill, 2012;Tait & Loosemore, 2012).…”
Section: Introductionmentioning
confidence: 99%